Variations in the Post-weaning Human Gut Metagenome Profile As Result of Bifidobacterium Acquisition in the Western Microbiome - Soverini, Matteo; Rampelli, Simone; Turroni, Silvia; Schnorr, Stephanie L.; Quercia, Sara; Castagnetti, Andrea; Biagi, Elena; Brigidi, Patrizia; Candela, Marco (Frontiers in Microbiology, 2016)
Studies of the gut microbiome variation among human populations revealed the existence of robust compositional and functional layouts matching the three subsistence strategies that describe a trajectory of changes across our recent evolutionary history: hunting and gathering, rural agriculture, and urban post-industrialized agriculture. In particular, beside the overall reduction of ecosystem diversity, the gut microbiome of Western industrial populations is typically characterized by the loss of Treponema and the acquisition of Bifidobacterium as an abundant inhabitant of the post-weaning gut microbial ecosystem. In order to advance the hypothesis about the possible adaptive nature of this exchange, here we explore specific functional attributes that correspond to the mutually exclusive presence of Treponema and Bifidobacterium using publically available gut metagenomic data from Hadza hunter-gatherers and urban industrial Italians. According to our findings, Bifidobacterium provides the enteric ecosystem with a diverse panel of saccharolytic functions, well suited to the array of gluco- and galacto-based saccharides that abound in the Western diet. On the other hand, the metagenomic functions assigned to Treponema are more predictive of a capacity to incorporate complex polysaccharides, such as those found in unrefined plant foods, which are consistently incorporated in the Hadza diet. Finally, unlike Treponema, the Bifidobacterium metagenome functions include genes that permit the establishment of microbe-host immunological cross-talk, suggesting recent co-evolutionary events between the human immune system and Bifidobacterium that are adaptive in the context of agricultural subsistence and sedentary societies.